Cheiromyces ananthgiriensis sp. nov. and Vanibandha gen. nov. from India - I.K. KUNWAR and D.K. AGARWAL, C. MANOHARACHARY*, N.K. RAO (Indian Phytopathology, 2006)
A new species of Cheiromyces and a new genus Vanibandha are proposed. The species of Cheiromyces described differs from the other species in having strictly 3 armed cheiroid conidia, lesser number of cells in each arm, thick, verruculose or echinulate wall, larger size of the conidia and conical conidiogenous cells. These characters warrant its placement in a new species. Hence, the fungus in discussion is described as a new species of Cheiromyces viz. C. ananthgiriensis. The new anamorphic genus Vanibandha is characterized by synnematous conidiophores with monoblastic conidiogenous cells producing hyaline one celled, narrowly elliptic or ovoid conidia. It is described with the type species V. sundara.